Measuring fraud in insurance industry: The case of automobile insurance in Taiwan - Li, Chu-Shiu; Peng, Sheng-Chang; Liu, Chwen-Chi (2007)
By conducting an extensive exploration on claim data, this paper attempts to investigate the fraud problem in Taiwan automobile physical damage insurance. Based on the different claim patterns between data in calendar year and policy year, excess claims are significantly identified in the last month of policy year. Censored regression provides robust estimation concerning the sources of the fraud payment.